2017
DOI: 10.15547/bjvm.952
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Escherichia coli isolates from healthy and diarrhoeic calves in Mashhad, Iran.

Abstract: Escherichia coli is a normal inhabitant of the gastrointestinal tract of vertebrates. Certain Escherichia coli strains have been associated with neonatal diarrhoea in ruminants. These strains can be assigned to one of the four main phylogenetic groups, A, B1, B2 and D. Several studies have shown the relationship between phylogeny and pathogenicity of E. coli, a great deal can be obtained by determining the phylogroup of unknown E. coli strains. In this study, we aimed to evaluate the influence of diarrhoea on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations. 23 In contrast to a previous study 1 that reported subgroup B2 3 as only present in the human and B2 especially B2 3 as a good index of human fecal pollution, our results showed that subgroup B2 3 was found among isolates from both calves (healthy) and dairy cows. Similarly, another study showed that E. coli isolates of ruminants (sheep, goat, calves, and cattle) and dogs belonged to the subgroup B2 3 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations. 23 In contrast to a previous study 1 that reported subgroup B2 3 as only present in the human and B2 especially B2 3 as a good index of human fecal pollution, our results showed that subgroup B2 3 was found among isolates from both calves (healthy) and dairy cows. Similarly, another study showed that E. coli isolates of ruminants (sheep, goat, calves, and cattle) and dogs belonged to the subgroup B2 3 .…”
Section: Discussioncontrasting
confidence: 99%
“…These results were almost similar to other studies which demonstrated that the isolates of phylogroup A were prevalent in the intestinal tracts of most animals 24,37 and phylogroup B1 was dominant among isolates from healthy cattle. 38 In accordance with the previous reports in Iran, 23,39 this study showed that the phylogroup B1 was dominant in calves. The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the strains belonging to B 1 group cannot be ignored and presence and distribution of such bacteria in feces of wild birds can be a potential hazard for humans that are in contact with them (19). There is much documented evidence showing that extension of E. coli phylogroups and virulence genes are not accidental in different hosts, and frequency of phylogenetic groups in hosts is influenced by some factors including host characteristics and food regimen, the antibiotic pressure in each geographic region, ecological differences, body volume, and climate conditions (20,21). EscobarParamo et al (2006) analyzed E. coli strains from fecal samples of birds, human, and other mammals and observed the significant distribution of phylogroups D and B 1 in birds droplets and A and B 2 in human strains (22).…”
Section: Discussionmentioning
confidence: 99%